1999
DOI: 10.1001/archinte.159.1.71
|View full text |Cite
|
Sign up to set email alerts
|

Iatrogenic Diseases as a Reason for Admission to the Intensive Care Unit

Abstract: Background: Data on iatrogenic diseases (IDs) have been recorded for the past 25 years. We determined whether aging of the general population and medical advances, including more powerful drugs and complex procedures, have altered the incidence, causes, and consequences of severe IDs during this period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
1
6

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(61 citation statements)
references
References 51 publications
1
53
1
6
Order By: Relevance
“…4 Classen states that, although adverse events seem to occur in a small proportion of antibiotic courses, the frequency of antibiotic use makes them account for 23% of all adverse events recorded. 5 The overall incidence of ADRs to antimicrobials in our study was 6.12%.…”
Section: Discussionmentioning
confidence: 99%
“…4 Classen states that, although adverse events seem to occur in a small proportion of antibiotic courses, the frequency of antibiotic use makes them account for 23% of all adverse events recorded. 5 The overall incidence of ADRs to antimicrobials in our study was 6.12%.…”
Section: Discussionmentioning
confidence: 99%
“…26 An iatrogenic event was caused by drugs or by medical and/or surgical acts performed in accordance with standards of care during a patient's ICU stay. 28 Infections were considered nosocomial if they first appeared 48 hours or more after hospital admission or within 30 days after previous discharge. An event was considered preventable when the MMC discussion led to the consensus conclusions that it could have been avoided because it was the consequence of acts or prescriptions made without respecting state-of-the-art medical and nursing standards of practice or that it was caused by equipment failure.…”
Section: Definitionsmentioning
confidence: 99%
“…An event was considered preventable when the MMC discussion led to the consensus conclusions that it could have been avoided because it was the consequence of acts or prescriptions made without respecting state-of-the-art medical and nursing standards of practice or that it was caused by equipment failure. 28,29 Preventability was assessed as an "error in management due to failure to follow accepted practice at an individual or system level." Accepted practice was taken to be "the current level of expected performance for the average practitioner or system that manages the condition in question."…”
Section: Definitionsmentioning
confidence: 99%
“…Numerous studies in the United States, the United Kingdom, and European countries have demonstrated that patients are frequently hospitalized as a result of medication-related problems that were preventable. [1][2][3][4][5][6][7][8] Studies have also shown that pharmacists are able to identify, resolve, prevent, and reduce medication errors. [9][10][11] The Institute of Medicine (IOM) has stated, "Health care has safety and quality problems because it relies on outmoded systems of work.…”
Section: Introductionmentioning
confidence: 99%